Protective Effect of Vitamin C against Infancy Rat Corneal Injury Caused by Acute UVB Irradiation. (27th May 2020) - Chen, Wei; Guo, Jianying; Guo, Haiyi; Kong, Xue; Bai, Jing; Long, Pan
Abstract : Purpose . Studies have shown that corneas of young children were more susceptible to Ultraviolet B (UVB) radiation damage. However, there exist limited information about the harm of UVB to eyes and preventive measures on infancy. Vitamin C as an antioxidant is widely used to prevent many diseases. Therefore, the aim of this study was to explore the protective effect of vitamin C on the cornea of infant rats with acute UVB injury. Method . Thirty-six infant rats were randomly divided into three groups: control (CON) group, UVB (UVB) group, and UVB+vitamin C (UVB+VitC) group. The UVB group was exposed to UVB irradiation (8 J/cm 2, 15 min/d, 7 d) and the UVB+vitamin C group suffered the same UVB irradiation treated with vitamin C at the dose of 40 mg/kg via intraperitoneal injection. Then, corneal morphology was detected in vivo and in vitro at 7 d post-UVB exposure. Furthermore, serum inflammatory factors (IL-1, IL-6, and TNF- α ) and oxidative status (4-HNE and MDA) were detected by ELISA, and the expression of vascular endothelial growth factor- α (VEGF- α ) and superoxide dismutase (SOD) in the cornea was detected by western blot or immunofluorescent staining. Results . Slit lamp detection revealed that the area of corneal desquamation and corneal neovascularization in the UVB+VitC group was significantly less than those in the UVB group at 7 d post-UVB exposure (all p < 0.05 ). OCT results showed that the thickness of the central cornea in the UVB+VitC group was decreased than that in the UVB group (p < 0.05 ). The serum inflammatory factors (IL-1, IL-6, and TNF- α ) and oxidative status (4-HNE and MDA) in the UVB group were significantly increased compared with the CON group (all p < 0.05 ), while those factors in the UVB+VitC group were decreased compared with those in the UVB group. Furthermore, the expression of VEGF- α in the UVB+VitC group was dramatically decreased compared with that in the UVB group (p < 0.05 ), and the expression of SOD2 in the UVB+VitC group was dramatically increased compared with that in the UVB group at 7 d post-UVB exposure (p < 0.05 ). Conclusion . Vitamin C could protect infant rats from corneal injury induced by UVB via alleviating corneal edema, improving corneal inflammatory reaction, and decreasing VEGF- α expression.